In Situ Monitoring of Lithium Metal Anodes and Their Solid Electrolyte Interphases by Transmission Electron Microscopy. Issue 6 (2nd May 2021) - Chen, Chih-Yao; Tsuda, Tetsuya; Oshima, Yoshifumi; Kuwabata, Susumu
Abstract : Lithium (Li) metal anodes (LMAs) are considered to be the holy grail of electrodes to enable advanced battery chemistry for energy‐intensive applications. However, the formation of Li dendrites and their intricate interplay with the solid electrolyte interphase (SEI) remain unclear to date. Herein, a simple yet efficient methodology for in situ transmission electron microscopy (TEM) observation is reported, and the relationship between the SEI chemistry and the morphology of LMAs is unraveled by a combination of TEM imaging and selected area electron diffraction analysis in an unprecedented way. The authors find that the coexistence of LiF and Li3 N in the SEI layer helps realize dendrite‐free Li deposition and directly visualize the deposition–dissolution behavior of individual Li deposits with different microstructures. The approach should be applicable to scrutinize a broad range of interfacial reactions in nonvolatile electrolytes (e.g., ionic liquid, glass‐, and ceramic‐based electrolytes) relevant to future energy storage devices, including magnesium secondary batteries. Abstract : A new transmission electron microscopy methodology is presented to accurately monitor the morphology evolution of lithium metal anodes and their solid electrolyte interphases (SEIs) under realistic operation conditions. This method combines the advantages of conventional open‐cell (high‐resolution visualization) and liquid‐cell approaches (better mimicking a real battery), which will expedite the development of next‐generation electrode materials.